Potential Therapeutic Effects of Flavonoids in Cardiovascular Disorders: Review - Singh, Sonia; Ahuja, Ashima; Varshney, Mahima (Current Hypertension Reviews, 2025)
IntroductionFlavonoids in various fruits and vegetables exert multifaceted biological effects. They are widely explored for cardiovascular, antitumor, antioxidant, antibacterial, antifungal, neuroprotective, and anti-inflammatory effects. Flavonoid cardioprotection is helpful in the management of myocardial injury, stroke, atherosclerosis, hypertension, and ischemia. Cardiovascular disease (CVD) has become a global threat in recent years due to increased mortality and morbidity rates. The increased mortality due to CVD among women, children, and poor economic groups has boosted the socio-economic burden on health care. Various researchers have explored the commercial applications of flavonoids, including quercetin, apigenin, luteolin, and catechin, as dietary supplements.MethodsThe findings were searched in the Google Scholar, Scopus, PubMed, and PubChem databases.ResultsPreclinical and clinical investigations have promoted the safety of flavonoids, such as apigenin and quercetin, for use as nutraceuticals that promote health. Flavonoids and their potential mechanisms of action and clinical applications offer insights for researchers and scientists to explore in the fields of medical and nanomedicine sciences. Nanomedicine, like liposomes, carbon nanotubes, nanosponges, and nanoparticles containing flavonoids, is used for its efficacy, potency, and target delivery.DiscussionFlavonols have the potential to regulate vasodilation and prevent apoptosis. Furthermore, their supplementation may reduce the risk of cardiovascular complications. Flavonoids function as antioxidants and exhibit potent anti-inflammatory effects by mediating inflammatory pathways, thereby contributing to the management of cardiovascular complications. Emerging evidence from researchers suggests flavonoids improve endothelial function and reduce blood pressure. Furthermore, flavonoids derived from cocoa, such as catechins, and those found in tea also enhance endothelial function. Nanosystems can enhance the solubility, permeability, and effectiveness of flavonoids as antioxidants, while also promoting controlled drug delivery. Nanoformulations can enhance the effects of morin, rutin, quercetin, and other flavonoids, significantly improving therapeutic outcomes.ConclusionThese findings offer researchers and scientists a novel technological approach utilizing flavonoids to address metabolic syndromes and related health conditions, thereby supporting personalized care and improving patient outcomes.
Keywords: Flavonoids